Values of local wisdom in Rambu Solo" from the perspective of Pentecostal spirituality and character education - Pantan, Frans (HTS teologiese studies, 2024)
The ceremony of Rambu Solo ’, a traditional Torajan funeral ritual, is often met with scepticism by Christians, particularly within the Pentecostal community, due to perceived spiritistic elements conflicting with Christian doctrines. Despite this, the deep-rooted cultural significance of Rambu Solo ’ persists among the Torajan people, including Pentecostals. This necessitates exploring aspects of the ceremony that align with Pentecostal values of spirituality and character education. Therefore, studies are needed that show the dimensions of spirituality and character education that Pentecostal believers can accept. The research method used in this article was qualitative ethnography, and the analysis used was the theological triad in Steven Jack Land’s Pentecostal spirituality, namely orthodoxy, orthopathy and orthopraxy. Findings revealed a divergence between Rambu Solo’s orthodoxy and Christian tenets. Nonetheless, aspects of orthopathy and orthopraxy within the Rambu Solo ’ ceremony align with Pentecostal spirituality, mainly through its emphasis on character education. Contribution: Using triad theology in assessing local culture in Indonesia provides a more comprehensive meaning of cultural values for constructing spirituality and character education.